Learning in the workplace: Use of informal feedback cues in doctor‐patient communication. Issue 9 (20th April 2020) - Sehlbach, Carolin; Teunissen, Pim W.; Driessen, Erik W.; Mitchell, Sharon; Rohde, Gernot G. U.; Smeenk, Frank W. J. M.; Govaerts, Marjan J. B.
Abstract: Objectives: We expect physicians to be lifelong learners. Participation in clinical practice is an important potential source of that learning. To support physicians in this process, a better understanding of how they learn in clinical practice is necessary. This study investigates how physicians recognise and use informal feedback from interactions with patients in outpatient settings as learning cues to adjust their communication behaviours in daily practice. Methods: To understand physicians' use of informal feedback, we combined non‐participant observations with semi‐structured interviews. We enrolled 10 respiratory physicians and observed 100 physician‐patient interactions at two teaching hospitals in the Netherlands. Data collection and analysis were performed iteratively according to the principles of constructivist grounded theory. Results: Following stages of open, axial and selective coding, we were able to conceptualise how physicians use cues to reflect on and adjust their communication. In addition to vast variations within and across patient encounters, we observed recurring adjustments in physicians' communication behaviours in response to specific informal feedback cues. Physicians recognised and used these cues to self‐monitor communication performance. They had established 'communication repertoires' based on multiple patient interactions, which many saw as learning opportunities contributing to the development of expertise. Our findings, however, show differences in physicians' individual levels of sensitivity in recognising and using learning opportunities in daily practice, which were further influenced by contextual, personal and interpersonal factors. Whereas some described themselves as having little inclination to change, others used critical incidents to fine‐tune their communication repertoires, and yet others constantly reshaped them, seeking learning opportunities in their daily work. Conclusions: There is large variation in how physicians use learning cues from daily practice. To enhance learning in and from daily practice, we propose turning workplace learning into a collaborative effort with the aim of increasing awareness and the use of informal performance‐relevant feedback. Abstract : Sehlbach et al. use observations and interviews to examine how physicians use informal feedback for professional development, highlighting how workplace learning could be improved through collaboration.